Diverse Biological Activity of Benzofuroxan/Sterically Hindered Phenols Hybrids - Elena Chugunova; Elmira Gibadullina; Kirill Matylitsky; Baurat Bazarbayev; Margarita Neganova; Konstantin Volcho; Artem Rogachev; Nurgali Akylbekov; Hoang Bao Tran Nguyen; Alexandra Voloshina; Anna Lyubina; Syumbelya Amerhanova; et al. (MDPI AG, 2023)
Combining two pharmacophores in a molecule can lead to useful synergistic effects. Herein, we show hybrid systems that combine sterically hindered phenols with dinitrobenzofuroxan fragments exhibit a broad range of biological activities. The modular assembly of such phenol/benzofuroxan hybrids allows variations in the phenol/benzofuroxan ratio. Interestingly, the antimicrobial activity only appears when at least two benzofuroxan moieties are introduced per phenol. The most potent of the synthesized compounds exhibit high cytotoxicity against human duodenal adenocarcinoma (HuTu 80), human breast adenocarcinoma (MCF-7), and human cervical carcinoma cell lines. This toxicity is associated with the induction of apoptosis via the internal mitochondrial pathway and an increase in ROS production. Encouragingly, the index of selectivity relative to healthy tissues exceeds that for the reference drugs Doxorubicin and Sorafenib. The biostability of the leading compounds in whole mice blood is sufficiently high for their future quantification in biological matrices.